Ras-induced hyperplasia occurs with mutation of p53, but activated ras and myc together can induce carcinoma without p53 mutation. - Lu, X; Park, S; Thompson, T; Lane, D (1992)
Using a reconstituted mouse prostate organ, the effects on endogenous p53 expression of the ras oncogene or of the ras + myc oncogenes were investigated. In this system the ras gene alone causes mild hyperplasia, but the combination of ras and myc leads to the formation of carcinomas. Surprisingly, while p53 mutations were found in cells derived from the reconstituted organs containing ras alone, no such mutations were found in the ras + myc-transformed cells. Their growth, unlike that of the cells containing ras alone, was not inhibited by transfection with plasmids encoding wild-type human p53. We suggest that expression of both activated ras and myc genes bypasses the need for p53 mutation by neutralizing the tumor suppressor activity of normal p53.